Lifestyle mobilities intersections of travel, leisure and migration - Duncan, Tara; Cohen, Scott A.; Thulemark, Maria (Farnham, Surrey, England Ashgate, 2013)
Being mobile in today's world is influenced by many aspects including transnational ties, increased ease of access to transport, growing accessibility to technology, knowledge and information and changing socio-cultural outlooks and values. Bringing together scholars from geography, sociology, tourism, history and beyond.
Introducing lifestyle mobilities / Scott A. Cohen -- Part 1. Corporeal performance -- Peripatetic artists : creative mobility and resourceful displacement / Claudia Bell -- Others have the clock but we have the time : alternative lifestyle mobilities and the resurgence of hitchhiking / Michael O'Regan -- 'Dirtbags' : mobility, community and rock climbing as performative of identity / Jillian M. Rickly-Boyd -- From (dis)embodied journeys to 'artscapes' : belly dancing as a digital 'travelling culture' / Rodanthi Tzanelli -- Part 2. Applying mobile methods -- Choosing their own paths : mobile methodologies for understanding your lifestyles / Katherine King -- Investigating perpetual travel : email interviews and longitudinal methods in travel, tourism and mobilities research / Garth Lean -- Travelling in the Caucasus : mobile methodologies and lifestyles in the field / Eleni Sideri -- Part 3. Moorings, mobilities and belonging -- Traveller trails : locating the lifestyle traveller / Kathryn Erskine -- Trans-Pacific bluewater sailors-exemplar of a mobile lifestyle community / Barbara A. Koth -- Mobile habitations of canoescapes / Jessica Dunkin -- From citizens to wanderers of the world : the Noguchi case as a timely study on cosmopolitanism / Elia Ntaousani -- Part 4. Complexities of wider identities -- Mobilities, lifestyles and imagined worlds: exploring the terrain of lifestyle migration / Norman McIntyre -- Storm watching : making sense of Clayoquot sound winter mobilities / Phillip Vannini -- Negotiating tourist identities : mobilities in an age of climate change / Stewart Barr -- Respect for nature at 200 km/h? Exploring the role of lifestyle mobilities in environmental responsibility / Leslie Mahon -- Lifestyle mobilities: conclusgtions and future research / Maria Thulemark.
Includes bibliographical references and index.
Keywords: Tourism; Leisure; Migation, Internal; Social mobility